Robotic assisted cytoreductive surgery, removal of a recurrent disease in the right pericaval lymph node in a patient with ovarian cancer with the robotic Xi platform - Massoud Shoraka; Hadeer Metwally; Semiramis Carbajal-Mamani; Joel Cardenas-Goicoechea (Korean Society of Obstetrics and Gynecology, 2021)
Objective The standard approach for recurrent ovarian cancer is laparotomy. In this video, we present a cytoreductive surgery using the robotic Xi platform to remove a 2.7 cm pericaval tumor. Methods A narrative video demonstration of robotic-assisted surgery to remove recurrent ovarian cancer in a pericaval lymph node. A 62-year-old female presented with recurrent carcinoma of the pericaval lymph node. After 40 months of surveillance, the patient was asymptomatic, but a computed tomography (CT) scan showed an isolated mass (2.7×2.3 cm) in the right pericaval lymph node. Her cancer antigen (CA)-125 level increased from 26 to 46 U/mL. The robotic Xi platform was used to remove the metastatic lymph nodes. The first step was diagnostic laparoscopy. The second step was robotic port placement below the umbilicus. The third step was dissection and identification of landmarks, and the last step was removal of the tumor and closure. Results The metastatic lymph nodes were removed. The patient was discharged on postoperative day 1 and had no postoperative complications. Her CA-125 level dropped to 17 U/mL two weeks after surgery. Pathology showed metastatic high-grade serous carcinoma in one lymph node, consistent with the patient's known primary. Two additional lymph nodes were removed and negative for carcinoma. Pelvic washings were negative for malignancy. Conclusion Robotic-assisted surgery is safe and feasible in selected patients with isolated recurrent disease.